1998
DOI: 10.1016/s0735-1097(98)00416-1
|View full text |Cite
|
Sign up to set email alerts
|

Vascular reactivity is impaired in genetic females taking high-dose androgens

Abstract: Long-term treatment with high-dose androgens is associated with impaired vascular reactivity in genetic females, consistent with a deleterious effect of androgen excess on arterial physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 27 publications
3
89
3
1
Order By: Relevance
“…27,28 Genetic females taking androgens have larger arteries than control females. 29 Androgen-deprivation therapy in genetic males is associated with smaller brachial artery size compared with control males. 30 These findings support the notion that sex hormone balance has different, and under certain circumstances opposite, effects on conduit artery remodeling with an androgen state causing positive remodeling compared with an estrogen state.…”
Section: Estrogen and Sex/gender-related Differences In Blood Vesselsmentioning
confidence: 99%
“…27,28 Genetic females taking androgens have larger arteries than control females. 29 Androgen-deprivation therapy in genetic males is associated with smaller brachial artery size compared with control males. 30 These findings support the notion that sex hormone balance has different, and under certain circumstances opposite, effects on conduit artery remodeling with an androgen state causing positive remodeling compared with an estrogen state.…”
Section: Estrogen and Sex/gender-related Differences In Blood Vesselsmentioning
confidence: 99%
“…In fact, in a preliminary study, we observed that the plasma testosterone level was not related to FMD in postmenopausal women (unpublished observation). It has been reported that testosterone may impair endothelial function in women, and especially in young women with polycystic ovary syndrome (34) and women taking high-dose androgens (35). Aortic rings obtained from female rats treated with testosterone showed a significant decrease in prostacyclin synthesis (36), supporting the idea that testosterone influences vasoconstriction in women.…”
Section: Discussionmentioning
confidence: 75%
“…Testosterone may act as a direct vasorelaxant through influence on the vascular wall endocrine/ paracrine factors. 32,[36][37][38] It is also reported that the vasorelaxing effect of testosterone is endothelium independent, with the possible involvement of potassium channel modulation. 39,40 There is a pressing need for epidemiological studies in Africa, to determine the risk factors for the development of hypertension in specific living circumstances.…”
Section: Introductionmentioning
confidence: 99%